Una Nuova Esperienza the ABS-CBN Studio Complex - Mendoza, Loren April Y.; Balane, Ronald S. (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
Television was introduced in the Philippines in 1953 with the opening of DZAQ-TV Channel 3 of Alto Broadcasting System in Manila. This television station was later bought by the Chronicle Broadcasting Network, which started operating radio stations in 1956. The acquisition signaled the birth of ABS-CBN Broadcasting Network, now considered one of the major broadcasting companies not only in the Philippines but also in Asia. From all generations, entertainment, television, movies, all these have played an important role in the evolution of the Philippine's national identity. It created a forum for uniquely Filipino stories to be played out and allowed Filipinos to share different cultural experiences. It also provided a direct channel for values, humor and style to influence our society. The new ABS-CBN Studio Complex's mission is to produce and handle production and post-production phases of TV Networking in the best way that it can. It will enable the network to meet the multimedia company's expansion plans and provide facilities for the growing needs to serve the public. It does not only visions on catering broadcasting facilities for the local television but as well as international market as it progresses. To become state-of-the-art, is to become internationally renowned.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman